Pengaruh Disiplin dan Loyalitas Kerja Terhadap Kinerja Pegawai Dinas Perdagangan Kabupaten Bangkalan - Mukarromah, Rohmatul; Kuswinarno, Mudji (Eco-Entrepreneur, 2023)
This research was conducted on the employees of the Trade Office in Bangkalan Regency. The trade office is the government representative in the regional office responsible for assisting the government in the trade sector. Human resources must have good performance to achieve organizational goals. The decrease in employee performance is the current problem that exists in this office. Besides, working hour provision violations also happen and lead to a decline in discipline and work loyalty of the employees. The low level of employee loyalty can be indicated by the decrease in employee absenteeism. This study aims to determine the effect of Work Discipline on the Performance of Bangkalan Trade Office Employees, to determine the effect of Work Loyalty on the Performance of BangkalanTrade Office Employees, and to determine the effect of Discipline and Work Loyalty on the Performance of Bangkalan Trade Office Employees. The method used in this research was quantitative research. The population in this study was 52 employees, so this research was categorized as a population study. The data collection method employed interviews, questionnaires, and a literature study. Data analysis techniques used were validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that 1) Work Discipline has a positive and significant effect on Employee Performance with a t-count of 5.771 t-table of 1.67591, with a significant level of 0.000 0.05, and with a β value of 1.576. 2) Work Loyalty has a positive and significant effect on Employee Performance with a t-count of 2.900 t-table of 1.67591, with a significant level of 0.006 0.05, and with a β value of 0.863. 3) Discipline and work loyalty have a positive and significant effect on employee performance with an F-count of 65.173 t-table of 3.13 and with a significant level of 0.000 0.05.